2005
DOI: 10.1161/circulationaha.105.573550
|View full text |Cite
|
Sign up to set email alerts
|

Unfractionated and Low-Molecular-Weight Heparin as Adjuncts to Thrombolysis in Aspirin-Treated Patients With ST-Elevation Acute Myocardial Infarction

Abstract: Background-There is uncertainty about the role of intravenous unfractionated heparin (UFH) and low-molecular-weight heparin (LMWH) in patients with ST-elevation myocardial infarction (STEMI) treated with aspirin and thrombolysis. Methods and Results-We performed a meta-analysis of the randomized trials to assess the effect of UFH and LMWH on reinfarction, death, stroke, and bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(60 citation statements)
references
References 68 publications
2
51
0
7
Order By: Relevance
“…Nine randomized clinical trials 320,[331][332][333][334][335][336][337][338] and additional studies (including one meta-analyses) 339 document similar or improved composite outcomes (death, MI, and/or recurrent angina or recurrent ischemia or revascularization) when enoxaparin was administered instead of UFH to patients with STEMI undergoing fibrinolysis. This must be balanced against an increase in intracranial hemorrhage in patients Ͼ75 years of age who received enoxaparin documented in one of these randomized controlled trials.…”
Section: Unfractionated Heparin Versus Low-molecular-weight Heparin Wmentioning
confidence: 99%
“…Nine randomized clinical trials 320,[331][332][333][334][335][336][337][338] and additional studies (including one meta-analyses) 339 document similar or improved composite outcomes (death, MI, and/or recurrent angina or recurrent ischemia or revascularization) when enoxaparin was administered instead of UFH to patients with STEMI undergoing fibrinolysis. This must be balanced against an increase in intracranial hemorrhage in patients Ͼ75 years of age who received enoxaparin documented in one of these randomized controlled trials.…”
Section: Unfractionated Heparin Versus Low-molecular-weight Heparin Wmentioning
confidence: 99%
“…For example, a meta-analysis of 14 trials that involved Ͼ25 000 patients with STEMI examined the use of unfractionated heparin and LMWH when added to aspirin and fibrinolytic therapy. 103 Intravenous unfractionated heparin during hospitalization did not prevent reinfarction or death; however, LMWH given for 4 to 8 days reduced reinfarction by Ϸ25% and death by Ϸ10% compared with placebo and reduced reinfarction by almost one half when directly compared with unfractionated heparin. 103 The potential benefit of combination therapy with platelet GP IIb/IIIa inhibitors and fibrinolytics has been evaluated in STEMI patients both in angiographic trials [81][82][83][84] and in trials with "hard" clinical events as the primary outcome.…”
Section: Pharmacological Therapymentioning
confidence: 89%
“…103 Intravenous unfractionated heparin during hospitalization did not prevent reinfarction or death; however, LMWH given for 4 to 8 days reduced reinfarction by Ϸ25% and death by Ϸ10% compared with placebo and reduced reinfarction by almost one half when directly compared with unfractionated heparin. 103 The potential benefit of combination therapy with platelet GP IIb/IIIa inhibitors and fibrinolytics has been evaluated in STEMI patients both in angiographic trials [81][82][83][84] and in trials with "hard" clinical events as the primary outcome. 86 Although mortality trials using a reduced dose of reteplase (GUSTO-V) 86 or tenecteplase (Assessment of the Safety and Efficacy of a New Thrombolytic Regimen [ASSENT-3]) 74 showed that combined use of a GP IIb/IIIa inhibitor with a reduced-dose fibrinolytic enhanced coronary artery patency versus full-dose fibrinolytic therapy alone, combination therapy with these agents plus abciximab failed to show any early or late survival benefit over full-dose fibrinolytics alone or any reduction in the risk of intracranial hemorrhage.…”
Section: Pharmacological Therapymentioning
confidence: 89%
“…For patients with STEMI to be treated with fibrinolysis, 17 studies supported enoxaparin over UFH (LOE1 336,[387][388][389][390][391][392][393] ; LOE 2 341,394,395,396 ; LOE 4 397 ; LOE 5 393,396,398 -401 ) Twelve other studies were neutral comparing enoxaparin and UFH. [402][403][404][405][406][407][408][409][410][411] Reviparin.…”
Section: Consensus On Sciencementioning
confidence: 99%